The Experimental Study of The Effect of Air Preheating in MSW Pellet Multi-Stage Downdraft Gasifier - Depi Rustam Ependi; Arif Rahman Saleh; Bambang Sudarmanta (IPTEK The Journal for Technology and Science, 2019)
High municipal solid waste generation in Indonesia can be used to substitute fossil energy. MSW is converted into pellet form to uniform moisture content. This study aimed to improve the performance of gasified downdraft gasifier processes by heating air inlets in pyrolysis, oxidation, and reduction zones. Variations of air temperature inlet in these zones are 80 oC, 110 oC, 150 oC, and 210oC. The results of this study obtained the highest air temperature at 210 ºC for 969 ºC. The syn-gas compositions (CO and H2) at an increase in temperature of 80-210 ºC increased from 21.4%, 9.99%, and 1.77% to 22.79%, 10.28%, and 1, 79% respectively. Cold gas efficiency increased by 5.13 % and the lowest tar level was 34.39 mg/Nm3. Based on the result of research, preheated air can improve the efficiency of gasification and reduce tar content in the syngas.